Statistical Literacy of Pre-Service Primary Teachers: A Pre-experimental Research - Sidik, Geri Syahril; Nurkamilah, Milah; Apriani, Ika Fitri (Al-Mufid, 2023)
This study aims to investigate the effect of a problem-based learning (PBL) approach on statistical literacy in mathematics education, taking into account students' initial mathematical ability. The study used a pre-experimental research design with students categorized according to their initial mathematical ability (high, medium and low). The statistical literacy test scores of 60 students were analyzed using one-way ANOVA to assess differences between the groups. The results showed that students' initial mathematical ability significantly influenced their level of statistical literacy. The constructivism-based PBL approach shows potential for improving mathematical literacy, especially for students with low and medium initial mathematical ability. However, too much focus on constructivism theory and a lack of proper lesson planning may hinder the effectiveness of PBL implementation.